Guide for Resilient Energy Systems Design in Hot and Humid Climates - Zhivov, Alexander M. (ASHRAE, 2023)
HHC provide unique challenges to HVAC, plumbing, and thermal energy system designers. Considering facility operation in the context of high OA temperatures and humidity, system reliability and building resiliency cannot be understated. This Guide describes best practice examples of robust and reliable systems emphasizing redundancy, durability, and functionality. The target audience for this Guide is technical experts involved in building and energy systems design, renovation, operation, and maintenance; architectural and engineering professionals; and energy service companies. The content of this Guide may also be of interest to building owners, executive decision-makers, and energy managers of public, government, and military organizations. The Guide was developed with partial support from the DOD Environmental Security Technology Certification Program, the Office of the Deputy Assistant Secretary of the Army (Energy and Sustainability), and the International Energy Agency Energy in Buildings and Communities Program Annex 73.